"I don't think I took her fears seriously": Exploring the experiences of family members of individuals at‐risk of developing psychosis over 12 months. (9th June 2020) - Izon, Emma; Berry, Katherine; Law, Heather; Shiers, David; French, Paul
Abstract: Individuals with an at‐risk mental state (ARMS) of psychosis experience high levels of distress, anxiety, low mood, and suicidal ideation. Families of ARMS individuals provide significant support but are often neglected by services. This study is the first of its kind to use a novel longitudinal qualitative methodology to directly compare family/carers' earlier experiences supporting ARMS individuals to 12 months later. This provides a more ecologically valid insight into how perceptions change over time and how family/carers adapt. Semistructured interviews were conducted with 10 family/carers at two points within a 12‐month period. This study was embedded within a randomized control trial, the Individual and Family Cognitive Behavioural Therapy trial. Interview transcripts were analysed using thematic analysis, with a focus on how experiences and reactions for family/carers changed over time. Over 12 months, four factors were important for family/carers to facilitate their caring role. These were summarized in the thematic map (LACE model): L ooking after your own well‐being; A ccessing additional support from family intervention; C ommunicating openly with the individual; and E ngaging with services for the individual. All four aspects of the model were important in improving family communication, meeting family/carers' unmet needs, and helping them to feel more confident and less isolated in their carer role. Novel implications suggest that when feasible, services should involve family/carers of ARMS individuals in sessions and explore family/carer support strategies in managing their own distress. The most significant insight was the need to develop family/carer resources to educate, normalize, and validate their own experiences.